2020
DOI: 10.1017/s0007114520003104
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between energy intake, physical activity and UCP2 -866G/A gene variation on weight gain and changes in adiposity: an Indonesian Nutrigenetic Cohort (INDOGENIC)

Abstract: This study aimed to investigate an interaction between energy intake, physical activity, and UCP2 gene variation on weight gain and adiposity changes in Indonesian adults. This is a prospective cohort study conducted in 323 healthy adults living in the city of Yogyakarta, Indonesia. Energy intake, physical activity, body weight, body mass index (BMI), percent body fat, waist to hip ratio (WHR) were measured at baseline and after two years while and UCP2 -866G/A gene variation was determined at baseline. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…There were no significant interactions observed between UCP2 gene variations and any of the dietary factors on the obesity-related parameters; however, significant interaction depicting a positive correlation between UCP2 SNP rs659366 (−866G/A) GG genotype and total energy intake on body weight change (P interaction = 0.016) and BFP (P interaction = 0.034) was observed. The same study also showed significant interaction (P interaction = 0.040) between UCP2 SNP rs659366 (−866G/A) GG genotype and physical activity on WHR indicating that participants with increased physical activity and the UCP2 gene variant had lower WHR [29]. Further studies on larger populations are required to validate these results and elucidate the mechanisms.…”
Section: Malaysiamentioning
confidence: 81%
See 1 more Smart Citation
“…There were no significant interactions observed between UCP2 gene variations and any of the dietary factors on the obesity-related parameters; however, significant interaction depicting a positive correlation between UCP2 SNP rs659366 (−866G/A) GG genotype and total energy intake on body weight change (P interaction = 0.016) and BFP (P interaction = 0.034) was observed. The same study also showed significant interaction (P interaction = 0.040) between UCP2 SNP rs659366 (−866G/A) GG genotype and physical activity on WHR indicating that participants with increased physical activity and the UCP2 gene variant had lower WHR [29]. Further studies on larger populations are required to validate these results and elucidate the mechanisms.…”
Section: Malaysiamentioning
confidence: 81%
“…Seven studies analyzed gene-diet interactions on obesity-related parameters in the Indonesian population: four cross-sectional [12,21,31,32], two prospective cohort studies [29,33] and one case-control study [30].…”
Section: Indonesiamentioning
confidence: 99%
“…Four candidate gene studies showed that interactions between 4 different gene variants and low levels of PA were significantly associated with obesity-related anthropometrics ( 33 , 37 , 39 , 42 ). The study by Moore et al.…”
Section: Resultsmentioning
confidence: 99%
“…While results from nutrigenetic studies and studies investigating gene-physical activity interactions on obesity suggest there could be some consistent associations between eating patterns or low levels of PA and their genetic interactions on an increased risk of obesity, associations with specific gene variants were not replicated across studies. Across all included studies, statistically significant findings were reported for 12 individual SNPs, including FLJ33544 rs140133294 ( 43 ), FTO rs1421085 ( 29 , 37 ), rs9939609 ( 31 , 45 ), rs10163409 ( 33 ), rs3751812 ( 39 ), CARTPT rs2239670 ( 35 ), UCP2 rs659366 ( 42 ), CLOCK rs1801260 ( 36 ), MC4R rs17782313 ( 37 , 45 , 46 ), rs12970134 ( 40 , 46 ), TMEM18 rs7561317 and NEGR1 rs2815752 ( 37 ). However, these associations were either only significant in single trials or were not replicated in response to the same environmental exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation